Trajectories of Health-Related Quality of Life and HbA1c Values of Children and Adolescents With Diabetes Mellitus Type 1 Over 6 Months: A Longitudinal Observational Study - Fischer, Kathrin I.; Fischer, Felix H.; Barthel, Dana; Otto, Christiane; Thyen, Ute; Klein, Marcus; Walter, Otto; Ravens-Sieberer, Ulrike; Rose, Matthias; Nolte, Sandra (Frontiers in Pediatrics, 2020)
Background: To achieve optimized blood glucose levels (HbA1c) and high health-related quality of life (HRQL ), children and adolescents with diabetes mellitus type 1 (T1DM) must follow strict disease management strategies. This study aims to investigate HRQL of children and adolescents with T1DM and its association with HbA1c values over the course of six months. Methods: Patients aged 7 to 17 years (n=203) with T1DM provided HRQL data on a monthly basis. HRQL was measured using the Kids-CAT, a computer-adaptive test (CAT) comprising five generic HRQL domains. HbA1c values were assessed at baseline, at three and six months. We explored the trajectory of HRQL at the domain level using linear mixed effects models. Further, we investigated the association between HRQL and HbA1c values over time using path analysis models. Results: Children and adolescents with T1DM reported high scores across all HRQL domains over time. However, those with an HbA1C value of >9.0% reported significantly lower scores in physical well-being and parent relations compared with those with an HbA1C value of <7.5%. Path analysis models revealed a minimal temporal relationship between HbA1c and HRQL, with a small negative impact of HbA1c on physical well-being, psychological well-being and parent relations. Conclusion: Although observed HRQL of young patients with T1DM was comparable to age-related German-speaking reference population over the course of six months, those with an HbA1C value >9.0% reported lower scores in selected HRQL domains. Thus, special attention should be drawn to HRQL of children and adolescents with higher HbA1c values. The minimal relationship between HbA1c and HRQL indicates that the two therapy goals, i.e., achieve glycemic targets control and maintenance of high HRQL, should be considered and evaluated independently in clinical routine. Trial registration: DRKS00006326 (German Clinical Trial Register), date of registration: August 1st, 2014